2018
DOI: 10.2298/gensr1801021m
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing food security in arid areas of Pakistan through newly developed drought tolerant and short duration mustard (Brassica juncea L.) Canola

Abstract: Food security is the crucial global issue, especially in developing countries like Pakistan. Since edible oil is an essential food item, its persistent paucity in the country and huge import for meeting domestic requirements, has attained it second largest import item after petroleum products. The aim of present study is qualitative and quantitative evaluation of newly developed short duration and drought tolerant canola quality Brassica juncea lines ZBJ-06012 and ZBJ-08051 to overcome the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…shoot length, RPP = roots per plant, LA = leaf area Regression analysis was performed to evaluate the contribution of each studied trait for improving shoot length under drought stress conditions. It was found from our results (Table 5) that the root length contributed higher towards increasing shoot length as compared with other traits (Ali et al, 2016;Cakir, 2004;Mustafa et al, 2018) = 0.8534, R 2 = 0.6823, Adjusted R 2 = 0.6424, Standard Error = 0.0231 DRW = dry root weight, FRW = fresh root weight, RL= root length, RPP = roots per plant, LA = leaf area Conclusions It was found that the genotypes B-316 and Rakaposhi showed better performance for all studied traits especial shoot and root length as compared with other two genotypes EV-109Q and Pak-Afghoi. The minimum effects of drought were reported at control and 90% irrigation water.…”
Section: Resultsmentioning
confidence: 57%
“…shoot length, RPP = roots per plant, LA = leaf area Regression analysis was performed to evaluate the contribution of each studied trait for improving shoot length under drought stress conditions. It was found from our results (Table 5) that the root length contributed higher towards increasing shoot length as compared with other traits (Ali et al, 2016;Cakir, 2004;Mustafa et al, 2018) = 0.8534, R 2 = 0.6823, Adjusted R 2 = 0.6424, Standard Error = 0.0231 DRW = dry root weight, FRW = fresh root weight, RL= root length, RPP = roots per plant, LA = leaf area Conclusions It was found that the genotypes B-316 and Rakaposhi showed better performance for all studied traits especial shoot and root length as compared with other two genotypes EV-109Q and Pak-Afghoi. The minimum effects of drought were reported at control and 90% irrigation water.…”
Section: Resultsmentioning
confidence: 57%
“…Under abiotic stress conditions the wheat is highly affected which caused reduction in the yield and productivity. The salt stress caused cell membrane damage, production of toxic chemicals and accumulation of reactive oxygen species in the plant body (Ali et al, 2017;Ali and Malik, 2021;Khaliq et al, 2021;Mustafa et al, 2018;Sarwar et al, 2021). The salt or NaCl stress caused damage in the cell membranes, the use of salicylic acid induce the tolerance in the plant body which may help crop plants to withstand under salt and abiotic stress condition (Aaliya et al, 2016;Ali et al, 2015;Iqra et al, 2020;Majid et al, 2017;Mazhar et al, 2020;Sarwar et al, 2022;Zubair et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The canola quality oil from rapeseed and mustard is safe for human utilization and its meal is suitable for animal, birds, and aqua feed (Mustafa et al, 2022) The beginning of the canola quality rapeseed development and the rapid rise in worldwide rapeseed productivity started with the release of "Span, Oro, and Zephyr" cultivars in 1968, followed by the canola cultivars named, "Tower and Candel" in 1974. and several others (Tofanica, 2019). Canola version cultivars mostly belong to the rapeseed group worldwide, however, Oilseeds Research Institute (ORI), Faisalabad, Pakistan has also introduced the canola version varieties not only in rapeseed, but also developed the canola variety in mustard group with the name "AARI Canola" (Mustafa et al, 2018). Preference for the development of canola (00) in mustard is due to less maturity period, silique shattering resistance, and high temperature tolerance as compared with rapeseed.…”
Section: Introductionmentioning
confidence: 99%